Panorama of the Spanish narrative of 2006 (XXI Century. Spanish Literature and Culture, 2007)
This work reviews the most noteworthy Spanish novels of 2007. The article offers up areview of each novel, taking into account different thematic and formal aspects. Alongwith authors of large literary trajectories, readers will discover other who, through thesheer quality work alone, will delight them.
Keywords: novel; criticism; reality; fiction; recent history